Sustainable energy from the sea: A Comprehensive review of hybrid offshore solar, wind, and wave technologies - Kaur, Nisha; Sudhakar, K.; Mohd Rusllim, Mohamed; Cuce, Erdem; Barbulescu, Dan (Cerebration Science Publishing, 2026)
The increasing global demand for clean and sustainable energy has intensified research focus on offshore renewable energy systems, particularly those integrating wind, solar, and wave resources. Offshore hybrid renewable energy systems represent a transformative opportunity to harness diverse marine energy sources, aiming to improve energy yield, capacity factor, and reliability compared to single-technology solutions. Evaluation of past literature reveals a critical gap in comprehensive evaluations of fully integrated hybrid offshore platforms that simultaneously deploy floating solar photovoltaic (FPV), offshore wind turbines, and wave energy converters (WECs), including their techno-economic performance and environmental impacts. This study addresses this gap by systematically reviewing the current state-of-the-art offshore floating solar, wind, and wave energy technologies and analyzing key commercial pilot hybrid projects such as Hollandse Kust Noord, W2POWER, and the Hybrid Floating POSEIDON system. A mixed-methods approach combining qualitative literature review, multi-criteria technical, economic, and environmental evaluation, and case study analysis was employed to assess the design innovations, integration strategies, and deployment challenges. Results demonstrate that hybrid offshore systems leveraging synergies between solar, wind, and wave resources can achieve up to five times higher energy output than single-source systems, with floating wind currently leading in maturity and energy production scale, complemented effectively by floating solar and wave converters to enhance seasonal and operational stability. Novel modular floating platforms and advanced mooring systems enable scalable, durable solutions capable of withstanding harsh marine environments. Environmental considerations, including biofouling, corrosion, and ecosystem impacts, can be addressed via mitigation strategies and adaptive site selection.